The benefits of environmental change in a secure service for people with intellectual disabilities. Issue 5 (26th August 2014) - G. Long, Clive; Bell, Natalie; Carr, Alison; Cairns, Lisa; Webb, Amanda; Collins, Lesley
Abstract : Purpose: – The purpose of this paper is to assess the behavioural and psychological effects on people with intellectual disabilities of transferring to an environment influenced by patient choice and low secure standards. Design/methodology/approach: – Patients and staff transferring from a non-optimal environment to one driven by low secure standards compared the homeliness, ward climate and satisfaction with the two wards. Comparisons were made between the occurrences of risk behaviours on the two wards. Findings: – The new environment was rated by staff as more homely while patients' increased satisfaction with the new ward was reflected in social climate ratings of patient cohesion and experienced safety. The latter findings were reinforced by an objective reduction in risk behaviours in the new environment. Practical implications: – Treatment interventions need to optimise research findings that attest to the influence of the environment on the behaviour of patients with intellectual disabilities. Originality/value: – Findings highlight need to increase the focus on aspects of the built environment in planning the treatment of women in secure care.